Africa starts a fishing ‘revolution’ - Ernest Harsch (Africa Renewal, 2006)
At the base of the Zomba plateau in southern Malawi, more and more villagers are digging ponds to raise fish. Mr. James Chitonya previously grew maize, with meagre returns. But since he began practicing “fish farming” (also known as “aquaculture”) several years ago, he has earned enough from fish sales to replace his thatched grass hut with a house that has electricity and an iron-sheet roof. “I am also able to pay school fees for my children and buy them clothes,” he told a local reporter. “In addition, I have bought some livestock from the sales of fish.”